Une ébauche de sculpture ibérique dans les carrières de la Dame d’Elche - Cyril Gagnaison; Christian Montenat; Jesús Moratalla; Pierre Rouillard; Elisabeth Truszkowski (Mélanges de la Casa de Velázquez)
In March 2005, in the course of an examination of the quarry from which the stone used to sculpt the Lady of Elche was extracted, the bust of a young warrior in rough sculpture was discovered among the detritus at the bottom of the quarry. Fifty centimetres high, the bust displays the characteristic features of plastic works of art wrought in the south-eastern region of the Iberian Peninsula in the 5th-4th centuries BC: warrior iconography, organisation of volumes, rectangular face and maintenance of archaic frontality with asymmetry. This is the earliest known piece of Iberian rough sculpture.